Multiresolution Fusion Estimation of Dynamic Multiscale System Subject to Nonlinear Measurement Equation - Cui, Peiling; Pan, Quan; Wang, Guizeng; Cui, Jianfeng (Advances in Intelligent Computing, 2005)
Fusion of the states of a nonlinear dynamic multiscale system (DMS) on the basis of available noisy measurements is one of the well-known key problems in modern control theory. To the best of our knowledge, all of the previous work focused attention on linear DMS. However, nonlinear DMS has never been investigated. In this paper, modeling and fusion estimation of dynamic multiscale system subject to nonlinear measurement equation is proposed. Haar wavelet is used to link the scales. Monte Carlo simulation results demonstrate that the proposed algorithm is effective and powerful in this kind of nonlinear dynamic multiscale system estimation problem.